Women engaged in prostitution and COVID-19: why are they excluded from socially vulnerable groups? - Michelle Ishida Chiang; Maitê Leite Basile; Ana Beatriz Pereira de Souza; Isabella Dastler Moccagatta; Julia Rabello Guerra Vieira; Thaís Rocha Lourenço; Mariana Langanke Gonçalves; Helena Afférri Fernandes Pinto; Rosane Lowenthal; Michele Lacerda Pereira Ferrer; Giselle Burlamaqui Klautau (Universidade de São Paulo, 2022)
ABSTRACT This study analyzed the exposure of women engaged in prostitution in downtown São Paulo to COVID-19. This cross-sectional study had a convenience sample selected in May 2021. We interviewed 219, mostly black, middle-aged, poor women with comorbidities. Among them, 61 had shown COVID-19 symptoms, 23, tested positive for the disease, seven underwent hospitalization, and four reported post-COVID-19 complications. Only 26 (30.2%) had been vaccinated. In addition to gender, race, and class inequalities, these women suffer both from a higher risk of contracting COVID-19 due to their working conditions and from the subsequent worsening of that disease due to age and lack of vaccination.